Psychology in management accounting and control research: an overview of the recent literature - Lisa-Marie Wibbeke; Maik Lachmann (Journal of Management Control, 2020)
For decades, management accounting and control (MAC) researchers have employed a diverse set of source disciplines to predict and examine behavior, and psychology is among the most frequently drawn upon. Although the literature confirms that psychological theories are highly relevant to MAC research, the existing knowledge on this field remains fragmented. Given this background, we examine recent MAC research through a systematic review of the different subfields of psychology to investigate the development of this stream of research. To do so, we collect 125 relevant articles from nine leading accounting journals between 2000 and 2019 and analyze their contents. On this basis, we provide a detailed overview of the use of psychological theories in recent literature and identify links between specific theories and MAC topics. We find that the quantity and proportion of psychology-based MAC research and the diversity of psychology subfields all increase during our investigation period, especially between 2015 and the first half of 2019. Overall, most studies address performance measurement and evaluation topics, and social psychology concepts are the most frequently applied. However, we find considerable differences in the application of psychological theories across different MAC topics. Our review provides insights into the content of this research stream and, thus, serves as a valuable source for researchers seeking an overview of previous investigations drawing on different subfields of psychology.
Keywords: M41; 330; Management accounting; Management control; Psychology; Literature review